2022
DOI: 10.2147/ijgm.s372386
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with COVID-19 Vaccine Hesitancy in Uganda: A Population-Based Cross-Sectional Survey

Abstract: Purpose Vaccination toward coronavirus disease (COVID-19) has been recommended and adopted as one of the measures of reducing the spread of this novel disease worldwide. Despite this, vaccine uptake among the Ugandan population has been low with reasons surrounding this being unknown. This study aimed to investigate the factors associated with COVID-19 vaccine hesitancy in Uganda. Methods A cross-sectional study was conducted on a total of 1042 adults in the districts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Regarding the factors associated with completing the primary COVID-19 vaccination series, having more knowledge of COVID-19 was positively associated with vaccination uptake among the slum and estate communities. The finding is in line with previous studies that have also reported positive associations [ 9 , 11 ]. This is partly because individuals with good knowledge of the disease tend to be more aware of the importance of getting vaccinated and where to get the vaccine.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Regarding the factors associated with completing the primary COVID-19 vaccination series, having more knowledge of COVID-19 was positively associated with vaccination uptake among the slum and estate communities. The finding is in line with previous studies that have also reported positive associations [ 9 , 11 ]. This is partly because individuals with good knowledge of the disease tend to be more aware of the importance of getting vaccinated and where to get the vaccine.…”
Section: Discussionsupporting
confidence: 93%
“…The low uptake of COVID-19 vaccination has been attributed to concerns about the adverse effects and effectiveness of the vaccines [ 9 , 10 ]. Intriguingly, the inaccessibility of vaccination centers, global vaccine supply chain dynamics, and perceived misconceptions have been linked to low vaccine uptake, especially in low-income countries [ 11 , 12 , 13 ]. Nonetheless, vaccination remains the most effective intervention for curtailing communicable disease pandemics [ 14 ], and most countries have implemented COVID-19 vaccination programs [ 7 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study (30) focusing Kenya indicated that misinformation and lack of public sensitization about the vaccines had led to vaccine hesitancy. A study (31) focusing Uganda noted that due inadequate awareness on vaccination sites, the overall Covid-19 hesitancy was 58.6%. A study (32) focusing Kenya and other countries highlighted that Covid-19 acceptance rates ranged between 6.9 to 97.9%.…”
Section: Awareness Barriersmentioning
confidence: 99%